Internal Control System Analysis in The Complete Systematic Land Registration Program (PTSL) in Sukabumi District - Sari, Putri Permata; Suherman, Acep (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
This research aims to analyze the effectiveness of the internal control system in the Complete Systematic Land Registration Program (PTSL) in Sukabumi Regency. PTSL is a government initiative to speed up and simplify the land registration process, provide legal certainty, and increase the efficiency of land administration. In its implementation, this program is expected to overcome various obstacles that often occur in the land registration process. The research method used is descriptive qualitative with a case study approach. Data was collected through observation, interviews and documentation. Analysis was carried out on five components of internal control according to the COSO framework: control environment, risk assessment, control activities, information and communication, and monitoring. The research results show that even though the internal control system at PTSL Sukabumi Regency has been implemented, there are still several weaknesses that hinder the effectiveness of the program. The main obstacle is the lack of coordination between the village and ATR/BPN, as well as incomplete files which often occur during the registration process. This causes a lot of work to be delayed and unfinished. In addition, a weak internal control system causes communication problems and suboptimal supervision. This research concludes that to increase the effectiveness of PTSL, there needs to be improvements in the internal control system, increased coordination between related parties, and more intensive outreach to the public about the importance of complete land registration files. In this way, it is hoped that the PTSL program can run more effectively  and  efficiently, and  achieve  its  goal  of  providing  legal  certainty  and  prosperity  for  the community.